Leadership and democratisation : the case of Nelson Mandela in South Africa and Kim Dae-Jung in South Korea - Jeong, Young-Yun (Stellenbosch : University of Stellenbosch, 2011)
Dissertation (PhD)--University of Stellenbosch, 2004.